A Bibliometric Exploration of Behavioral Finance: Trends, Influental Authors, Research Themes, and Emerging Concepts - Rokhilawati, Yeny; Wardhani, Rachmasari Pramita; Rijal, Syamsu (IJBLE Scientific Publications Community Inc., 2024)
This bibliometric exploration delves into the evolving landscape of behavioral finance, employing a systematic analysis of scholarly publications from the past decade. The study maps key trends, influential authors, research themes, and emerging concepts within the interdisciplinary realm of behavioral finance, blending insights from psychology and economics. Through rigorous data collection and analysis using VOS Viewer, the research addresses four critical questions: identifying trends, profiling influential authors, categorizing research themes, and exploring potential future directions. The study reveals a dynamic field with a focus on psychological factors influencing financial decision-making. Key findings include influential authors such as Hirshleifer and Statman, thematic clusters encompassing market efficiency and investor sentiment, and emerging areas of interest like the impact of COVID-19 on financial behavior. The implications of this research extend to academia, practice, and policy, providing a valuable resource for navigating the complex landscape of behavioral finance.